Pentecostal Charismatic Pedagogy of Peter Hocken in Christian Religious Education - Majesty, Gilbert Timothy; Litos Sitorus Pane; Demsy Jura (International Journal of Christian Education and Philosophical Inquiry, 2025)
This article analyzes the Pentecostal charismatic pedagogy of Peter Hocken in the context of Christian Religious Education (CRE), focusing on the integration of the Holy Spirit's experience and a transformative learning approach. Through theological and pedagogical studies, this research examines how Hocken emphasizes the role of spiritual gifts, worship, and faith community as central elements in Christian Religious Education (CRE). Unlike the traditional cognitive-doctrinal model of Christian education, Hocken's approach offers a holistic experiential learning paradigm. This article also explores the challenges of its implementation, including criticism from a conservative theological perspective regarding the potential for subjectivity and the lack of emphasis on systematic doctrine. Furthermore, this research highlights the relevance of Hocken's pedagogy in the context of the global church, particularly in the Global South and Messianic Jewish communities, where charismatic dimensions and local cultures interact. The findings indicate that although this model provides a new dynamic for CRE, its success depends on the educators' ability to balance charismatic freedom with a measurable learning structure. This article concludes that Hocken's thinking not only enriches the discourse on Charismatic/Pentecostal education but also broadly challenges the church to rethink the approach to CRE in the contemporary era.